Mometasone furoate in the management of asthma: a review - Tan, Ricardo A (Dove Medical Press, 2008)
Inhaled corticosteroids (ICS) have proven to be the most effective and essential therapy for the treatment of bronchial asthma. The 2007 National Asthma Education and Prevention Program guidelines recommend ICS as preferred therapy for patients with mild to severe persistent asthma. Mometasone furoate (MF) is a relatively new ICS agent with high affinity for the glucocorticoid receptor. It is approved in the US for maintenance treatment of asthma for patients 4 years of age and older. It has been shown to be well tolerated with no significant adverse side effects observed in clinical trials and post-marketing surveillance. The efficacy of mometasone furoate has been established in large, well-designed studies. In patients with persistent asthma previously treated either with short-acting beta-agonists alone or twice-daily maintenance therapy with ICS, once-daily MF has been shown to be superior to placebo in improving lung function, symptom control, and quality of life; and has shown comparable efficacy compared with budesonide, beclomethasone, and fluticasone. Twice-daily dosing with MF has been demonstrated to successfully allow for reduction or elimination of oral corticosteroids in severe asthmatics.